An investigation on electric field emission in shielded capacitive coupler for wireless power transfer utilizing diverse materials - Ahmad, Suziana; Mohd Razib, Nurul Nadhirah; Mohd Yussoff, Nurul Hajar; Sadun, Amirul Syafiq (Wydawnictwo SIGMA-NOT, 2024)
This investigation proposes the utilization of diverse dielectric materials to reduce electric field emissions in shielded capacitive coupler for wireless power transfer. To identify the most influential dielectric materials in minimizing electric field emissions, Finite Element Analysis (FEA) was conducted. The dielectric materials incorporated in this proposed initiative encompass rubber, glass, FR4, halowax, air, mineral oil, and paper. These dielectrics served as separators between the coupler and the shielding plate. The work demonstrates the electric field emissions at various values in distinct locations of the exposure area, encompassing the top, bottom, and side of the coupler. The result shows the air is the most suitable insulator among all dielectric materials.